Persepsi Pemuda Tentang Keistimewaan Yogyakarta Bagi Ketahanan Politik Wilayah (Studi Pada Pengurus Karang Taruna Kabupaten Bantul Pariode 2014-2019) - Muhammad Pranasik Faihaan (Jurnal Ketahanan Nasional, 2015)
AbstractThe goals in this research were to knew the youth perceptions about the privilege of Yogyakarta for regional political resilience of Yogyakarta Special Region. The purpose of this study was to answered the research questions: regarding the condition Karang Taruna Bantul at district level and how the youth perceptions  about the privilege of Yogyakarta Special Region of Yogyakarta political resilience. This research was a field (field study research) using descriptive research method. The researcher did the collection of data using observation, in-depth interviews, and collection of documentation associated with the subject  and  object of research.The youth people  as a board of Karang Taruna Bantul supported, agreed and ready  to carried out the determination of the Sultan and Pakualam as governor. The impact of the youth's perception of the status of Yogyakarta privilege could be seen with the program  which many did several activities related to the privilege of Yogyakarta. Other support that was done by inserting a distinctive agenda in programs such as coming to socialized the laws and regulations derivative of privilege to the general public. The deferences of the youth perceptions was look at the opinion about Sultan Hamengku Buwono X succession. Allthough, There were diferent perceptions about The perceptions, The Regional political resilience in Yogyakarta Special Region remained relatively resilient to the legitimacy of the people of Yogyakarta and the central government.ABSTRAK Tujuan dalam penelitian ini adalah untuk mengetahui persepsi pemuda tentang keistimewaan Yogyakarta dan implikasinya bagi ketahanan politik Daerah Istimewaan Yogyakarta. Penelitian ini merupakan penelitian lapangan (field study research) dengan menggunakan metode penelitian diskriptif (descriptive research). Pengumpulan data menggunakan teknik observasi, wawancara mendalam, dan pengumpulan berbagai dokumentasi yang terkait dengan subjek maupun objek penelitian..Dampak dari persepsi pemuda terhadap status keistimewaan Yogyakarta bisa dilihat dengan program kerja Karang Taruna Kabupaten Bantul yang banyak melakukan berbagai kegiatan yang berkaitan dengan agenda keistimewan Yogyakarta. Pemuda yang duduk sebagai pengurus Karang Taruna Kabupaten Bantul mendukung, setuju dan siap melaksanakan penetapan Sri Sultan dan Pakualam sebagai gubernur. Dukungan lain yakni dilakukan dengan memasukkan agenda keistimewaan dalam program-program Karang Taruna Kabupaten Bantul seperti ikut mensosialisasikan UU serta peraturan turunan tentang keistimewaan kepada masyarakat luas. Perbedaan persepsi pemuda terihat jelas pada pandangan tentang suksesi kepemimpinan pasca Sri Sultan Hamengku Buwono X. Meskipun terjadi perbedaan persepsi tentang ketahanan politik wilayah di Daerah Istimewa Yogyakarta tetap relatif tangguh dengan adanya legitimasi dari rakyat Yogyakarta dan pemerintah pusat